Prevalence of Hazardous Occupational Noise Exposure, Hearing Loss, and Hearing Protection Usage Among a Representative Sample of Working Canadians. Issue 1 (January 2017) - Feder, Katya; Michaud, David; McNamee, James; Fitzpatrick, Elizabeth; Davies, Hugh; Leroux, Tony
Abstract : Objective: The aim of this study was to estimate the prevalence of hearing loss (HL), self-reported occupational noise exposure, and hearing protection usage among Canadians. Methods: In-person household interviews were conducted with 3666 participants, aged 16 to 79 years (1811 males) with 94% completing audiometry and distortion-product otoacoustic emission (DPOAE) evaluations. Occupational noise exposure was defined as hazardous when communicating with coworkers at an arm's length distance required speaking in a raised voice. Results: An estimated 42% of respondents reported hazardous occupational noise exposure; 10 years or more was associated with HL regardless of age, sex or education. Absent DPOAEs, tinnitus, and the Wilson audiometric notch were significantly more prevalent in hazardous workplace noise-exposed workers than in nonexposed. When mandatory, 80% reported wearing hearing protection. Conclusions: These findings are consistent with other industrialized countries, underscoring the need for ongoing awareness of noise-induced occupational HL.